Testes de vigor em sementes de girassol - Nunes, Henrique Dallava (2016)
For high agricultural yield of sunflower species (Helianthus annuus L.), some crop care should be taken, such as the use of high physiological quality seeds. The selection of lots made based on vigor tests becomes increasingly necessary for situations such as storage and sowing. Vigor tests in agricultural seed species were developed to meet a variety of purposes such as differentiating lots with similar germination percentages, stratifying different lots due to vigor, in the marketing of seeds and classification of lots in different levels of vigor in proportion to the behavior of the seeds expressed in seedling emergence, resistance to transport and storage xii potential. The most demanded features in a vigor test are: simplicity, low cost, speed and objectivity, and is replicable to allow comparison between results obtained by different analysts in different laboratories on data sent by the field. Mechanical damage at harvest, maturity of seeds, temperature and humidity at storage, types of seed bags, pest insects attack and disease incidences are factors that affect the vigor of a lot. A lot whit low physiological quality may trigger some problems in establishing the population of plants in crops such as emergency nonuniform seedlings, reduced germination rate, increased susceptibility to pathogens and increased vulnerability of seedlings possible weather events. Among the methods for evaluation of seed vigor are different types of test ranging from biochemical, physical and biological. The biochemical test electrical conductivity is fast and economical and evaluates the integrity of the plasma membrane of cells present in the seed tissues through the amount of solutes released in aqueous solution. Resistance tests like accelerated aging are essential in the study of seed vigor because analyze the germination behavior of the seed lots due to prolonged periods of high heat and humidity simulating the natural aging process. Physical tests such as X-ray have also been used due to its practicality and inability to injure the tissues of seeds, enabling subsequent germination tests.